Interacionismo sociodiscursivo: uma análise dos PCNs e da proposta curricular de Língua Portuguesa do estado de São Paulo - Cardoso, Rosana (2012)
The teaching of the Portuguese Language, for a long time, treated language as if it had, predominantly, the function of communicating or expressing thought. The aim was in the product; it was not given importance to the process. The studies and reflections of Mikhail M. Bakhtin (1992) brought new light to the problem because, for him, language should not be seen as a system; language is a social, historical and ideological phenomenon. The enunciation is the product of interaction between two people. Language is the place of interaction between author and reader, speaker and listener in a social communicative activity. The Russian philosopher defends the idea that language is dialogic, that means, there's always the presence of the other. Taking into consideration all these reflections, our objective is to conduct a literature review of documents related to the educational sphere, especially the National Curricular Parameters (PCN, 1997) about Portuguese Language in the second cycle of teaching and the Curriculum Proposal of São Paulo state, launched in 2008. The reflections and findings of Mikhail Bakhtin are used to support the studies about social discursive interaction, that is the base of our work. The studies of Bakhtin (1981) and Bronckart (2006) will be taken as theoretical support . Regarding the text concepts that the authors mentioned above, we could verify that the texts appear in society belonging to textual genres that relate the person who enunciates with specific social activities. The proposal to study the language considered as a social activity, a place of interaction between people in a given communication context, implies an understanding of enunciation as central part of all language system. What is interesting related to the social interaction theory is the ideological game of interaction, in which discourses and texts are built in the exchange of world views of each other. The methodology consisted of a qualitative analysis of the educational proposals of Portuguese Language PCNs in the second cycle of basic education and the Portuguese Language Curriculum Proposal of São Paulo state. With this research, we verify the contributions brought by these educational proposals for the teaching of Portuguese language and we discuss, based on its statements, the effects of the principles related to interaction in the development of reading and writing skills of high school students.